2019
DOI: 10.1111/dth.13022
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment with photodynamic therapy of cutaneous leishmaniasis: A case report

Abstract: Leishmaniasis is a vector borne disease transmitted by phlebotomine sandflies. Cutaneous leishmaniasis (CL) predominantly causes skin ulcers but may disseminate. CL may present a therapeutic challenge. The present study reports the case of a 15‐year old boy with CL consisting of a single, ulcer on the leg, resistant to pentavalent antimony, oral fluconazole and topical ketoconazole therapy. Repeated photodynamic therapy using aminolevulinic acid resulted in complete healing of the ulcer, suggesting utility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 15 publications
1
22
1
Order By: Relevance
“…The ulcero-crusted form of CL was found to be more frequent (105; 73.7%), followed by the papulonodular form (30; 21.1%), and lastly the impetigenous form (7; 5.2%) (Table -5). These results are in agreement with those reported by previous studies [25,26]. The latter study found that the ulcerated form has the most common presentation.…”
Section: Resultssupporting
confidence: 94%
“…The ulcero-crusted form of CL was found to be more frequent (105; 73.7%), followed by the papulonodular form (30; 21.1%), and lastly the impetigenous form (7; 5.2%) (Table -5). These results are in agreement with those reported by previous studies [25,26]. The latter study found that the ulcerated form has the most common presentation.…”
Section: Resultssupporting
confidence: 94%
“…The use of PDT as an alternative therapeutic approach was justified by several reports that demonstrated some success in treating superficial CL. [9][10][11] In the present case, after initial failure of firstline liposomal amphotericin B therapy, sensitized PDT alone did not cure the condition. However, the first sessions of PDT resulted in significant reduction in size of the lesion, possibly due to the 7-day association with posaconazole.…”
Section: Discussioncontrasting
confidence: 55%
“…He was previously resistant to pentavalent antimony, oral fluconazole and local ketoconazole. His ulcer healed completely after repeated ALA-PDT ( Figure 6 ) ( 115 ). Compared with systemic therapy, this method should be considered as an attractive antiparasitic treatment, especially for drug-resistant cases.…”
Section: The Effects Of the Photosensitizer-based Therapies On Human ...mentioning
confidence: 99%